Calcium phosphate cement scaffold with stem cell co-culture and prevascularization for dental and craniofacial bone tissue engineering. Issue 7 (July 2019) - Lin, Ying; Huang, Shuheng; Zou, Rui; Gao, Xianling; Ruan, Jianping; Weir, Michael D.; Reynolds, Mark A.; Qin, Wei; Chang, Xiaofeng; Fu, Haijun; Xu, Hockin H.K.
Abstract: Objective: Calcium phosphate cements (CPCs) mimic nanostructured bone minerals and are promising for dental, craniofacial and orthopedic applications. Vascularization plays a critical role in bone regeneration. This article represents the first review on cutting-edge research on prevascularization of CPC scaffolds to enhance bone regeneration. Methods: This article first presented the prevascularization of CPC scaffolds. Then the co-culture of two cell types in CPC scaffolds was discussed. Subsequently, to further enhance the prevascularization efficacy, tri-culture of three different cell types in CPC scaffolds was presented. Results: (1) Arg–Gly–Asp (RGD) incorporation in CPC bone cement scaffold greatly enhanced cell affinity and bone prevascularization; (2) By introducing endothelial cells into the culture of osteogenic cells (co-culture of two different cell types, or bi-culture) in CPC scaffold, the bone defect area underwent much better angiogenic and osteogenic processes when compared to mono-culture; (3) Tri-culture with an additional cell type of perivascular cells (such as pericytes) resulted in a substantially enhanced prevascularization of CPC scaffolds in vitro and more new bone and blood vessels in vivo, compared to bi-culture. Furthermore, biological cell crosstalk and capillary-like structure formation made critical contributions to the bi-culture system. In addition, the pericytes in the tri-culture system substantially promoted stability and maturation of the primary vascular network. Significance: The novel approach of CPC scaffolds with stem cell bi-culture and tri-culture is of great significance in the regeneration of dental, craniofacial and orthopedic defects in clinical practice.